Radial Growth Periodicity of Selected Tropical Trees Grown in Mata Ayer, Perlis and Kepong, Selangor, Malaysia - Abdul A'zim, Amir A'ffan (2011)
Radial growth periodicity of Azadirachta excelsa Jack. Jacobs, Hopea odorata Roxb., and Khaya ivorensis A. Chev. grown in North Peninsular Malaysia (NPM)and West Peninsular Malaysia (WPM) were investigated. Three methods, dendrometer, knife-cutting method and collection of wood blocks from living tree were applied along with phenological observation and wood anatomical investigation. Meteorological data of the experimental period were also obtained. A. excelsa (NPM) showed seasonal radial growth pattern based on the dendrometer measurement. This was considered to have close relation with the uniform shedding of leaves in middle of December 2008 until the end of February 2009. A. excelsa (WPM) also showed seasonal radial growth pattern, but not uniform as in NPM. This was considered that the shedding of leaves occurred separately among individuals. H.odorata (NPM) showed seasonal radial growth. This was considered as the influenced of dried water drainage beside plot. As A. excelsa in WPM, H. odorata (WPM) also showed weak seasonal radial growth pattern, but the period of gradual slows down of radial growth was different for each individuals. K. ivorensis (NPM and WPM) showed continuous radial growth pattern. A. excelsa (NPM) showed seasonal cambial activity when the cells number in cambial and enlarging zone decreased in November 2008 and February 2009. Pattern of anticlinal division and enlarged vessel element were observed in August 2008,November 2008 and May 2009. A. excelsa (WPM) showed no seasonal cambial activity, even in shedding of leaves period. H. odorata (NPM) showed similar seasonal cambial activity as in A. excelsa (NPM). H. odorata (WPM) showed continuous cambial activity. Enlarged vessel element was observed in each month and axial resin canal was observed to be formed in November 2008 and February 2009. K. ivorensis (NPM and WPM) showed active cambial activity, even growing in less amount of rainfall. Enlarge vessel element was observed almost in each month. Band of axial parenchyma with large vessels diameter was investigated as ring structure in A. excelsa (NPM) while band of axial parenchyma with small to medium vessels diameter was observed in A. excelsa (WPM). Extension of tangential band alongside marking made in February 2009 was estimated as ring-like structure in A.excelsa (NPM) when the anatomical features were similar as its ring structure. Ring structure of H. odorata (NPM) was featured by band of axial parenchyma with resin canals while band of thick walled fibre cells in H. odorata (WPM). In K. ivorensis (NPM), the ring structure was characterized by wider band of thick walled fibre cells with small vessel diameter while narrower band of thick fibre cells with larger vessel diameter in K. ivorensis (WPM). No clear tangential band can be estimated for H.odorata and K. ivorensis as ring-like structure. Traumatic resin canals were easily formed in H. odorata and K. ivorensis, especially in rainy period. The highest positive correlation between radial growths with meteorological conditions was relative humidity in NPM and precipitation in WPM. Further field investigation and laboratory experiment are needed to deepen the understanding of radial growth periodicity in tropical trees.